Providing active haptic feedback in two dimensions on a touch screen - Alma, Uğur Alican. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
In this thesis, a two dimensional active electrostatic tactile display, which is capable of applying directional forces in two dimensions to a stationary nger, is analyzed. Directional forces are created using friction induced by electrostatic attraction. At the beginning, a shaker is used to move the tactile display in one dimension relative to the stationary nger in order to investigate the factors a ecting active feedback such as relative displacement, frequency of excitation signal, and amplitude of the excitation signal. In the rst step, minimum relative displacement necessary for directional force is examined. In the second step, lateral forces are measured for four distinct frequencies of electrostatic excitation. In the third step, the e ect of the amplitude of excitation voltage is investigated. The results show the feasibility of creating active feedback on an electrostatic tactile display. Minimum relative displacement is found as 4 mm. Increasing frequency and amplitude of electrostatic signal lead to the higher value of the directional force. Following the set of experiments investigating the active feedback in one dimension, a planar mechanism is built to move the tactile display in two dimensions relative to a stationary nger. In order to clearly see the e ect of orientation of the directional force with respect to the stationary nger, the tactile display is excited from 0 to 180 degrees with 45 degree increments. Besides, directional force is applied at 27 degrees to a stationary nger in a single experiment to investigate the feasibility of directional force at a small angle. The results show that active feedback is created in two dimensions on the electrostatic tactile display.
Keywords: Touch screens.